Editorial: Understanding the successful co-ordination of team behavior (Frontiers in Psychology, 2017)
More Stable Ties or Better Structure? An Examination of the Impact of Co-author Network on Team Knowledge Creation Mingze Li, Xiaoli Zhuang, Wenxing Liu and Pengcheng Zhang